Impact of multiplicity of infection and baculovirus co-infection ratio on recombinant adeno-associated virus vector production in insect cells - Schrama, Mels; de Jong, Linda A.; Kint, Stefan; Puri, Pranav; Hoeksema, Femke; Pijlman, Gorben P.; van Oers, Monique M.; Wijffels, Rene H.; Martens, Dirk E. (Frontiers in Bioengineering and Biotechnology, 2025)
Recombinant adeno-associated virus vectors (rAAVs) play an important role in gene therapy for the effective delivery of therapeutic genes into target cells. The Baculovirus Expression Vector System (BEVS) has gained significant attention for its versatility and scalability as an rAAV production platform. The existing Dual-Bac system uses two separate baculovirus constructs (Bac-GOI-ITR and Bac-Rep-Cap), each carrying essential genetic elements for rAAV production in insect cells. This study investigated how two infection parameters of the Dual-Bac system, the total Multiplicity of Infection (MOI) and the baculovirus co-infection ratio, influence rAAV production efficiency. Different budded virus (BV) concentrations were used to explore the effects on assembled rAAV capsid and encapsidated transgenic genome yields. An excess of Bac-Rep-Cap in synchronous co-infection produced high-quality rAAVs, whereas increasing the ratio of Bac-GOI-ITR to Bac-Rep-Cap resulted in more empty rAAV capsids. The optimal BV ratio varied with the total MOI used for co-infection, and when applying a BV ratio of one, MOI variations had a minimal impact on rAAV quality. These findings highlight the importance of optimizing the MOI and BV ratio to enhance rAAV yield and quality, contributing to more robust gene therapy production.